A Model Suggestion For Customer Saticfaction in the Proces of Using Mobile Shoping Applications: The Role of Personal Innovativeness as a moderator - Çarıkçıoğlu, Peyami Safa; Yüksel, Cenk Arsun (My University, 2018)
This study examines the relations: consumers' price sensitivity and perceived ease of use is related to customer satisfaction and also personal innovativeness has some effects on these relations, in purchases made by mobile applications. Research on consumer behavior in the field of electronic commerce is widely discussed in the literature. But, in the field of mobile commerce, there are few studies analyzing the behavior of information systems, especially for shopping with mobile applications. If information systems are successfully managed, ways will be made to achieve the desired goal, marketing strategies and channels, sales and more. Thus, it would be advantageous to make mobile technology easy to use, measuring the price sensitivity that affects purchasing decisions, ensuring the adoption of new information systems to enable users to shop with mobile applications. When the variables reach a satisfactory level, mobile marketing will be considered successful. Taking these variables into consideration, an improved model to this research is proposed. Therewith, (N=612) mobile users were questioned in the survey study and used Structural Equation Modeling (SEM) in AMOS program. In the research results, it is found that personal innovativeness is the most influential variable on customer satisfaction about mobile shopping applications. It has also been observed that in shopping by mobile applications, the perceived ease of use and price sensitivity are moderators of personal innovativeness in customer satisfaction. Personal innovativeness is a moderator variable which has a positive effect and it increases customer satisfaction.
Keywords: Customer Satisfaction; Price Sensitivity; Personal Innovativeness; Perceived Ease of Use; Mobile Shopping Applications; Müşteri Memnuniyeti; Fiyat Hassasiyeti; Kişisel Yenilikçilik; Algılanan Kullanım Kolaylığı; Mobil Alışveriş Uygulamaları